Attitude Toward Research and Patient Provider Choice in the Academic Institution: A Latent Class Analysis [15L]. (May 2016) - Wheeler, Sarahn; Sloane, Richard; Brown, Haywood L.; Heine, R. Phillips; Murtha, Amy
Abstract : INTRODUCTION: Understanding the impact of an academic institution's research mission on patient choice is critical to the sustainability of academic health care institutions. Therefore, our objective was to evaluate the impact of research reputation and opportunities to participate in clinical research on patient choice. METHODS: Patients seen for obstetric and gynecologic care were sent an online survey including demographics, factors affecting their provider choice, and the importance of opportunities to participate in clinical research. Latent class analysis (LCA), a statistical method used to identify subgroups with similar survey response patterns via multivariate categorical variable analysis, was performed. RESULTS: There were 493 OB, 780 GYN and 80 gyn-oncology patients. LCA identified 3 distinct response patterns. Group 1 (81% of respondents) was more likely to choose a provider based on recommendations and prior good experiences. Group 1 was also the most interested in research. Group 2 (11%) was more likely to choose a provider be based on convenience. Group 3 (8%) was least likely to be interested in research. All three groups reported they made healthcare/provider choices for themselves and there was no significant difference in race. CONCLUSION: Three distinct response patterns with unique motivators for provider choice and attitudes toward research were identified. Over 80% of respondent fell into a single response pattern in which our institution's reputation as a leader in research was considered important. These findings suggest the majority of our patients find the research mission and reputation of the institution gleaned from scholarly pursuit is important to their provider choice.